Utilitarian moral judgment in psychopathy - Koenigs, Michael (Oxford University Press, 2012)
Psychopathic behavior is characteristically amoral, but to date research studies have largely failed to identify any systematic differences in moral judgment capability between psychopaths and non-psychopaths. In this study, we investigate whether significant differences in moral judgment emerge when taking into account the phenotypic heterogeneity of the disorder through a well-validated distinction between psychopathic subtypes. Three groups of incarcerated participants [low-anxious psychopaths (n = 12), high-anxious psychopaths (n = 12) and non-psychopaths (n = 24)] completed a moral judgment test involving hypothetical dilemmas. The moral dilemmas featured ‘personal’ (i.e. involving direct physical harm) or ‘impersonal’ (i.e. involving indirect or remote harm) actions. Compared to non-psychopaths, both groups of psychopaths were significantly more likely to endorse the impersonal actions. However, only the low-anxious psychopaths were significantly more likely to endorse the personal harms when commission of the harm would maximize aggregate welfare—the ‘utilitarian’ choice. High-anxious psychopaths and non-psychopaths did not significantly differ in their personal moral judgments. These results provide novel laboratory evidence of abnormal moral judgment in psychopaths, as well as additional support for the importance of considering psychopathic subtypes.